2023
DOI: 10.3389/fonc.2023.1184021
|View full text |Cite
|
Sign up to set email alerts
|

Axillary lymph node dissection versus radiotherapy in breast cancer with positive sentinel nodes after neoadjuvant therapy (ADARNAT trial)

Amparo Garcia-Tejedor,
Carlos Ortega-Exposito,
Sira Salinas
et al.

Abstract: IntroductionBreast cancer surgery currently focuses on de-escalating treatment without compromising patient survival. Axillary radiotherapy (ART) now replaces axillary lymph node dissection (ALND) in patients with limited sentinel lymph node (SLN) involvement during the primary surgery, and this has significantly reduced the incidence of lymphedema without worsening the prognosis. However, patients treated with neoadjuvant systemic treatment (NST) cannot benefit from this option despite the low incidence of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
0
0
Order By: Relevance
“…without metastatic lymph nodes (cN0), 70-80% of these patients have pathologically cancer cell-free lymph nodes (pN0), increasing the risk of unnecessary procedures such as arm lymphedema, axillary sensory impairment, and shoulder adduction deficits. [28][29][30][31][32] This study found that the accuracy of SNLB compared to the histological examination from the axillary lymph node dissection showed a sensitivity of 82.8% and a specificity of 88%. This value is slightly different for patients who have had different types of biopsies.…”
mentioning
confidence: 68%
“…without metastatic lymph nodes (cN0), 70-80% of these patients have pathologically cancer cell-free lymph nodes (pN0), increasing the risk of unnecessary procedures such as arm lymphedema, axillary sensory impairment, and shoulder adduction deficits. [28][29][30][31][32] This study found that the accuracy of SNLB compared to the histological examination from the axillary lymph node dissection showed a sensitivity of 82.8% and a specificity of 88%. This value is slightly different for patients who have had different types of biopsies.…”
mentioning
confidence: 68%
“…However, there are two ongoing studies where patients who have SLNB positive after NACT are being randomized to receive either ALND or axillary radiotherapy. The results of the Alliance A011202 and the ADARNAT trial NCT04889924 [ 35 ] will be crucial to determine whether radiotherapy is non-inferior to ALND in terms of DFS and OS in patients with a positive SLNB after NACT. Research is ongoing in two trials: the Alliance A011202 and the ADARNAT trial NCT04889924.…”
Section: Discussionmentioning
confidence: 99%
“…These patients are randomized to ART or ALND, with the primary endpoint being the non-inferiority of axillary recurrence. A pilot phase including 100 patients was finalized in April 2023, and the accrual of the planned total of 1660 patients is ongoing [138].…”
Section: Patients With Residual Nodal Micro-and Macrometastasesmentioning
confidence: 99%